Mapeamento espacial e formulário digital de apoio à notificação da violência no Espírito Santo - Ceccon, Tamires Paulo (2024)
Introduction: Violence is a serious social and health problem, of high global and national relevance, affecting men and women in different ways and at different stages of life. The consequences of violence are perceived in health services by the costs and complexity of care they demand. Methodology: Observational epidemiological study of the ecological type carried out with the data of the notifications of the Information System of Diseases and Notification of the state of Espírito Santo, Brazil, between the years 2011 and 2021. The municipalities by year and age group were analyzed. The Health Technology developed was an Interactive Digital Form for guidance of health professionals, social assistance and education about the correct completion of the notification forms for interpersonal violence/ self-harm in the e-SUS VS system. Results: The average rate of notification of violence in ES was 14.05/10,000 inhab. The highest average rate of notification was in the group of adolescents (29.02/10,000 inhab), followed by adults (16.39/10,000 inhab), children (10.98/10,000 inhab) and the elderly (9.34/10,000 inhab). It is noticed that from 2012 to 2019 there was a median increase in violence notification rates for all age groups together. However, specifically for the group of 60 years and older, no age showed significant relationship with the notification of violence, thus, the notification rate is not influenced by the age. As for the interactive digital form it was created for guidance of health professionals and other notifying professionals, about the correct completion of the notification forms for interpersonal violence/self-harm in the e-SUS VS system. Conclusion: The mapping of violence notification rates evidenced in this study, offers a clear demonstration of the distribution of violence notifications in each municipality, and reinforce the need for investments in training and training on the notification of violence. The digital form to support notifying professionals represents a technology of great relevance for the notification process of violence and collaborates in complying with the legal requirements related to the notification of violence